Implementation Information System of Student Mobile Absention (SIMAMA) in Universitas Pembangunan Nasional “Veteran” Jawa Timur T. L. M. Suryanto - Suryanto, T. L. M.; A. Faroqi; Sari, N. K. (Nusantara Science and Technology Proceedings)
Improving the integrated management system of infrastructure and facilities is one of the service objectives of the Universitas Pembangunan Nasional “Veteran” Jawa Timur, the implementation is often still in the procedure manual stage, for example students must sign attendance as proof that the student is present and attending the lecture. Problems arise when recording UTS / UAS implementation where attendance is guided by a minimum of 75% with procedure manuals Students cannot see openly the number of attendance at the lecture, and not a few supervisors who use attendance as activist assessors in the class, with manual procedures for cheating opportunities in signatures the presence of the procedure manual by students at potentially very large lectures. Thus the need for an information system that can help resolve these problems. So in this study, it is intended to build a Student Attendance Mobile Information System (SIMAMA) which is useful for recording and displaying student attendance reports as an effort to improve integrated and computerized facilities and infrastructure.